The hepatitis C virus internal ribosome entry site facilitates efficient protein synthesis in blood vessel endothelium during tumour angiogenesis. - Chung, G; Yamada, Y; Pannell, R; Forster, A; Rabbitts, T (2003)
The development of gene delivery systems for therapeutic use involves vectors (often retrovirus or adenovirus) which typically encode one target protein, but the use of internal ribosome entry sites (IRES) can confer the ability to express more than one protein from bi- or polycistronic mRNAs. IRES elements can display tissue-specific expression, so it is necessary to determine suitable IRES for specific clinical applicability. Blood vessel endothelial cells are important clinically since many different conditions involve neo-vascularisation (angiogenesis). We have demonstrated that the viral hepatitis C IRES element is a powerful mediator of protein synthesis in angiogenesis, such as found in solid tumours. Homologous recombination was used to introduce IRES-lacZ sequences into the Lmo2 gene, which is expressed in endothelial cells. beta-Galactosidase expression was determined during vascular remodelling in mouse embryos and in sprouting endothelium during growth of solid tumours, and showed that the hepatitis C IRES is used efficiently for protein synthesis in endothelial cells. This IRES element can provide the means to express two or more therapeutic genes in blood vessel endothelium in clinical conditions, such as cancer, which depend on angiogenesis.